A question of feedback? Studying effects of academic performance and teacher feedback on primary school students' social acceptance in an experimental setting - Nicolay, Philipp; Huber, Christian (Frontiers in Education, 2023)
Introduction Being socially accepted by peers is a fundamental psychological need, and the consequences of social rejection are manifold. Investigating the causes of social rejection, a large body of studies have already established the relationship between social acceptance and individual characteristics (e.g., academic performance). However, the overall contributions of those individual characteristics are rather small, and the cause-and-effect relationship is still unclear. In addition, following social referencing theory, studies suggest that the feedback teachers give to students might also influence their social acceptance. Methods This experimental study, therefore, examined the influence academic performance, as well as teacher feedback, have on social acceptance. Teacher feedback was operationalized along the following two dimensions: feedback valence (positive/negative) and feedback focus (personal/task). A total of 737 third and fourth-grade primary school students (51% girls) from North Rhine-Westphalia (Germany) rated a fictional student's social acceptance on a scale of three sociometric items before and after watching an experimental video that showed a school day of the fictional student. Participants were randomly assigned to one level of academic performance (high/average/low) and one of four feedback conditions, with each being a combination of the two factors, feedback valence and feedback focus. Data were analyzed using linear mixed models. Results The results indicated that both academic performance and the valence of teacher feedback influenced participants' social acceptance of the student in the video. For instance, a high academic performance had a positive effect and a low academic performance had a negative effect on social acceptance. Further, positive teacher feedback influenced social acceptance positively, while negative teacher feedback influenced social acceptance negatively. However, this effect was moderated by the focus of the teacher's feedback. Feedback with a focus on the person had a more substantial effect on social acceptance for both positive and negative feedback than feedback with a focus on the task. Discussion These findings illustrate the importance teachers and their feedbacks have on students' peer relationships. They further suggest that it not only matters if teachers give positive or negative feedback but also how they do it.